Geosmithia argillacea: an Emerging Pathogen in Patients with Cystic Fibrosis - Giraud, Sandrine (American Society for Microbiology (ASM), 2010)
We report eight cases of airway colonization by Geosmithia argillacea in patients with cystic fibrosis. This filamentous fungus, resembling members of the genera Penicillium and Paecilomyces, was identified by molecular analysis. All patients carried a mutation on each CFTR (cystic fibrosis transmembrane conductance regulator) allele, with at least one copy of the F508del mutation. The first isolation of this fungus occurred from F508del-homozygous patients at a younger age than in F508del-heterozygous patients. Before recovery of G. argillacea, all patients were treated with itraconazole; two of them had also received voriconazole for an Aspergillus fumigatus infection. However, antifungal susceptibility patterns showed high MICs of voriconazole for all isolates, and high MICs of amphotericin B and itraconazole for the majority of them, but mostly low minimum effective concentrations (MECs) of caspofungin. The appearance and persistence of G. argillacea in the airways were not associated with exacerbation of the disease. However, the clinical implications of G. argillacea, particularly in immunocompromised patients, remain a concern, particularly given recent observations suggesting that this fungus may also cause disseminated infections.